DIETARY PATTERNS IN INFANCY MODIFY THE RISK OF CELIAC DISEASE - Aisha Sajid; Asim Ikram; Irum Akram (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVES To determine the association of various feeding and weaning patterns in infancy with celiac disease. METHODS: This was a case control study conducted at the department of Pediatrics, Madina Teaching Hospital, University Medical & Dental College, Faisalabad during 6 months period starting from January to June 2013. Data was collected from cases and controls meeting the inclusion criteria during period of six months. Relevant information was recorded on the predesigned questionnaire and analyzed by SPSS 19. P value <0.05 was considered significant. Odds ratio was calculated to find the association of breastfeeding and weaning with celiac disease. RESULTS: Duration of breastfeeding, age of weaning and amount of wheat introduction had statistically significant difference between cases and controls. (p. <0.001) the odds ratio for weaning earlier than 6 months was (OR 5.05, 95% CI, 2.23-11.43, p< 0.001). The odds of having celiac disease was more if wheat started in diet earlier than 6 months of age (OR 13.7, 95% CI: 3.7950.20, p=0.0001), delaying the wheat introduction between 6-12 months resulted in OR 10.54( 95% CI 3.63-30 p <0.0001). Duration of breastfeeding was significantly associated with anemia (p 0.016) Timing of gluten introduction was not associated significantly with the clinical spectrum of diseases. CONCLUSION: Clinical spectrum and incidence of celiac disease is affected by various feeding and weaning patterns in infancy. We need more studies to generate our own data regarding the association of our cultural foods with celiac disease. It will help us to build up our dietary and weaning recommendations during infancy.